Skin Biopsies in Gastrointestinal Diseases: A Single Centre Experience from North India - Shirazi, Nadia; Jindal, Rashmi; Ahmad, Sohaib (International Journal of Innovative Research in Medical Science, 2023)
Skin manifestations have always been alarming to the patient and often warrant complete clinical evaluation. A thorough understanding of relationship between gastrointestinal (GI) disorders and skin diseases can alert the clinician to an underlying occult GI disorder. The aim of the study was to review the cutaneous changes in patients with co-existent, often masked GI diseases and to observe the underlying pathophysiology of such lesions. This was a retrospective, record based observational study. The archived histopathology reports & medical records of patients over a period of 5 years were searched and all patients who underwent skin biopsy with co-existent GI diseases were included. Out of a total of 218 patients of GI diseases who had dermatological manifestations, only 44 were biopsied. Pruritis (n=175), koilonychia (n=52) and erythematous rash (n=35) were the most common clinical features. Psoriasis (n=4), vasculitis (n=4), Dermatitis Herpetiformis (n=3) and pyoderma gangrenosum (n=5) were often seen associated with benign GI diseases like Inflammatory Bowel Diseases, Chronic Liver Disease, Malabsorption syndrome etc. Sweets syndrome (n=2) and cutaneous metastatic nodules (n=3) were associated with underlying malignancy particularly of gall bladder and pancreas.